Separator, secondary battery, and electric device
Patent Information
- Application Number
- CN202380050205.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-17
- Publication Date
- 2025-02-18
AI Technical Summary
Existing secondary battery isolation films are prone to abnormal problems such as curling, curling, wrinkles, and tendons during production, processing and use, resulting in insufficient production yield and reliability of secondary batteries, poor heat resistance, and easy failure of the positive electrode. And negative electrode short circuit and fire and explosion accidents.
The isolation film design includes the first base film, the second base film and the adhesive layer, and the stiffness of the isolation film is made by adjusting parameters such as its transverse and longitudinal stiffness, fiber diameter, crystallinity, thickness, melting point and porosity. The degree is within a specific range, reducing the probability of abnormal problems and improving heat resistance and mechanical strength.
It improves the production yield and reliability of secondary batteries, reduces the probability of positive and negative short circuits and safety accidents, improves the heat resistance and mechanical strength of the isolation film, and enhances the safety performance of the battery.
Smart Images

Figure CN119487690A_ABST
Abstract
Description
Separator, secondary battery and electrical device Technical Field
[0001] The present application relates to an isolation film, a secondary battery and an electrical device. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage systems such as hydropower, thermal, wind, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. With the application and promotion of secondary batteries, the requirements for their reliability have become increasingly stringent.
[0003] Summary of the Invention
[0004] The present application provides an isolation film, a secondary battery, and an electrical device, which can improve the production yield of the secondary battery and also improve the reliability of the secondary battery.
[0005] In a first aspect, the present application provides an isolation film, comprising a first base film, a second base film, and an adhesive layer, wherein the adhesive layer is arranged between the first base film and the second base film; the stiffness of the isolation film in the transverse direction is recorded as T0, and the stiffness of the isolation film in the longitudinal direction is recorded as M0, then T0 is 1.0-8.0mN×cm, and M0 is 1.2-7.0mN×cm.
[0006] When a separator comprises a first base film, a second base film, and an adhesive layer positioned between the first and second base films, and has a transverse stiffness T0 of 1.0 mN×cm to 8.0 mN×cm and a longitudinal stiffness M0 of 1.2 mN×cm to 7.0 mN×cm, the separator can reduce the probability of abnormalities such as curling, curling, wrinkling, and tautness during separator production, processing, slitting, and secondary battery preparation, maintaining a regular morphology and thereby improving the production yield of secondary batteries. Furthermore, the separator's dimensions can be more accurately controlled, reducing the probability of localized shorting of the processed separator, thereby reducing the probability of positive and negative electrode short circuits and the probability of secondary battery fires and explosions, thereby improving the reliability of the secondary battery. Furthermore, the separator has excellent heat resistance and high mechanical strength. When used in a secondary battery, dendrites growing on the negative electrode side are less likely to pierce the separator. Furthermore, the separator has a low thermal shrinkage, thereby improving the reliability of the secondary battery. Therefore, the isolation film provided by the embodiments of the present application can improve the production yield of the secondary battery and can also improve the reliability of the secondary battery.
[0007] In any embodiment of the present application, the stiffness T0 of the isolation film in the transverse direction is 1.7-5.0 mN×cm, and can be optionally 1.9-4.7 mN×cm.
[0008] In any embodiment of the present application, the stiffness M0 of the isolation film in the longitudinal direction is 1.2-4.0 mN×cm, and can be optionally 1.5-3.3 mN×cm.
[0009] This can further improve the heat resistance of the isolation membrane, improve the reliability of the secondary battery, and also improve the production yield of the secondary battery.
[0010] In any embodiment of the present application, T0 / M0 is 1.0-2.5, and can be optionally 1.2-2.0, thereby further improving the heat resistance of the separator, improving the reliability of the secondary battery, and improving the production yield of the secondary battery.
[0011] In any embodiment of the present application, the stiffness of the first base film in the transverse direction is recorded as T1, and T1 is 0.25-4.5 mN×cm, and can be optionally 0.9-3.0 mN×cm.
[0012] In any embodiment of the present application, the stiffness of the first base film in the longitudinal direction is recorded as M1, and M1 is 0.15-4.0 mN×cm, and can be optionally 0.6-3.0 mN×cm.
[0013] In any embodiment of the present application, T1 / M1 is 1.0-3.0, and can be optionally 1.2-2.0.
[0014] By adjusting the stiffness T1 in the transverse direction, the stiffness M1 in the longitudinal direction and the ratio T1 / M1 of the first base film within the above range, the heat resistance of the isolation membrane can be further improved, the reliability of the secondary battery can be improved, and the production yield of the secondary battery can also be improved.
[0015] In any embodiment of the present application, the stiffness of the second base film in the transverse direction is recorded as T2, and T2 is 0.3-5.0 mN×cm, and can be optionally 0.8-3.5 mN×cm.
[0016] In any embodiment of the present application, the stiffness of the second base film in the longitudinal direction is recorded as M2, and M2 is 0.2-4.5 mN×cm, and can be optionally 0.5-3.0 mN×cm.
[0017] In any embodiment of the present application, T2 / M2 is 1.0-3.5, and can be optionally 1.1-1.9.
[0018] By adjusting the stiffness T2 in the transverse direction, the stiffness M2 in the longitudinal direction and the ratio T2 / M2 of the second base film within the above range, the heat resistance of the isolation membrane can be further improved, the reliability of the secondary battery can be improved, and the production yield of the secondary battery can also be improved.
[0019] In any embodiment of the present application, the average fiber filament diameter of the first base membrane is 80-300 nm, and can be optionally 100-280 nm.
[0020] In any embodiment of the present application, the average fiber diameter of the second base membrane is 100-300 nm, and can be optionally 120-280 nm.
[0021] By adjusting the average fiber filament diameter of the first base membrane and / or the average fiber filament diameter of the second base membrane within the above range, the stiffness of the first base membrane, the second base membrane and the isolation membrane can be adjusted, and the isolation membrane can also have good heat resistance and high ionic conductivity, thereby improving the reliability of the secondary battery and the electrochemical performance of the secondary battery.
[0022] In any embodiment of the present application, the ratio of the crystallinity of the second base film to the crystallinity of the first base film is greater than 1, and can be optionally 1.03-1.5, and more optionally 1.05-1.25.
[0023] The first base film of the isolation membrane faces the negative electrode and the second base film faces the positive electrode. By adjusting the ratio of the crystallinity of the second base film to the crystallinity of the first base film to be greater than 1, the stiffness of the first base film, the second base film and the isolation membrane can be adjusted, which is also beneficial to the preparation of a wound electrode assembly.
[0024] In any embodiment of the present application, the crystallinity of the first base film is 33%-70%, and can be optionally 35%-45%.
[0025] In any embodiment of the present application, the crystallinity of the second base film is 35%-80%, and optionally 40%-55%.
[0026] By adjusting the crystallinity of the first base film and / or the crystallinity of the second base film within the above range, the stiffness of the first base film, the second base film and the isolation film can be adjusted, and the isolation film can also have good mechanical strength and elasticity, which is beneficial to improving the high temperature resistance and reliability of the secondary battery and is also beneficial to the preparation of a wound electrode assembly.
[0027] In any embodiment of the present application, the ratio of the thickness of the second base film to the thickness of the first base film is greater than 1, and can be selected from 1.02 to 5.0, and more preferably from 1.2 to 2.5.
[0028] The first base film of the isolation membrane faces the negative electrode and the second base film faces the positive electrode. By adjusting the ratio of the thickness of the second base film to the thickness of the first base film to be greater than 1, the stiffness of the first base film, the second base film and the isolation membrane can be adjusted; in addition, the thickness of the first base film is relatively small, and the stretching ratio during preparation is usually large, so the orientation degree of the first base film is higher and the physical strength (such as puncture strength, etc.) is higher. Therefore, when it faces the negative electrode, it can better alleviate dendrite growth and improve the reliability of the secondary battery.
[0029] In any embodiment of the present application, the thickness of the first base film is less than or equal to 12 μm, and can be optionally 2.5-5 μm.
[0030] In any embodiment of the present application, the thickness of the second base film is less than or equal to 14 μm, and can be optionally 3-6 μm.
[0031] By adjusting the thickness of the first base film and / or the thickness of the second base film within the above range, the stiffness of the first base film, the second base film and the separator can be adjusted, which is also beneficial for the secondary battery to have a high energy density.
[0032] In any embodiment of the present application, the ratio of the melting point of the first base film to the melting point of the second base film is less than 1, and can be optionally 0.2-0.95, and more optionally 0.35-0.90.
[0033] The first base film of the isolation membrane faces the negative electrode and the second base film faces the positive electrode. By adjusting the ratio of the melting point of the first base film and the melting point of the second base film to be less than 1, the stiffness of the first base film, the second base film and the isolation membrane can be adjusted; in addition, the melting point of the first base film is low and the physical strength (such as puncture strength) is high, so when it faces the negative electrode, it can better alleviate dendrite growth and improve the reliability of the secondary battery.
[0034] In any embodiment of the present application, the melting point of the first base film is greater than or equal to 110°C, and can be optionally 120°C-165°C.
[0035] In any embodiment of the present application, the melting point of the second base film is greater than or equal to 150°C, and can be optionally 165°C-330°C.
[0036] By adjusting the melting point of the first base film and / or the melting point of the second base film within the above range, the stiffness of the first base film, the second base film and the isolation film can be adjusted, and the isolation film can also have good closed-cell properties, which is beneficial to improving the reliability of the secondary battery.
[0037] In any embodiment of the present application, the ratio of the porosity of the second base film to the porosity of the first base film is greater than 1, and can be optionally 1.01-2.8, and more optionally 1.1-2.0.
[0038] The first base film of the isolation membrane faces the negative electrode and the second base film faces the positive electrode. By adjusting the ratio of the porosity of the second base film to the porosity of the first base film to be greater than 1, the stiffness of the first base film, the second base film and the isolation membrane can be adjusted; in addition, the first base film with smaller porosity faces the negative electrode, which can also better alleviate dendrite growth and improve the reliability of the secondary battery.
[0039] In any embodiment of the present application, the porosity of the first base film is 28%-70%, and can be optionally 30%-50%.
[0040] In any embodiment of the present application, the porosity of the second base film is 30%-80%, and can be optionally 35%-60%.
[0041] By adjusting the porosity of the first base membrane and / or the porosity of the second base membrane within the above range, the stiffness of the first base membrane, the second base membrane and the isolation membrane can be adjusted, and the isolation membrane can also have good ionic conductivity, which also helps to improve the cycle performance, kinetic performance, etc. of the secondary battery.
[0042] In any embodiment of the present application, the porosity of the isolation membrane is 27%-65%, and optionally 33%-55%.
[0043] In any embodiment of the present application, the ratio of the average pore size of the second base film to the average pore size of the first base film is greater than 1, and can be optionally 1.05-2.5, and more optionally 1.1-2.
[0044] The first base membrane of the isolation membrane faces the negative electrode and the second base membrane faces the positive electrode. By adjusting the ratio of the average pore size of the second base membrane to the average pore size of the first base membrane to be greater than 1, the stiffness of the first base membrane, the second base membrane and the isolation membrane can be adjusted; in addition, the first base membrane with a smaller average pore size faces the negative electrode, which can better alleviate the growth of dendrites and better homogenize the ion flow from the positive electrode, thereby reducing the problems of rapid dendrite growth and overly sharp dendrite morphology due to excessive ion concentration in local positions of the negative electrode, and also helps to improve the cycle performance and kinetic performance of the secondary battery.
[0045] In any embodiment of the present application, the average pore size of the first base film is 48-1800 nm, and can be optionally 50-300 nm.
[0046] In any embodiment of the present application, the average pore size of the second base film is 50-2000 nm, and can be optionally 100-400 nm.
[0047] By adjusting the average pore size of the first base membrane and / or the average pore size of the second base membrane within the above range, the stiffness of the first base membrane, the second base membrane and the isolation membrane can be adjusted; the first base membrane and the second base membrane can also better alleviate the growth of dendrites and improve the reliability of the secondary battery; the isolation membrane can also have good ionic conductivity, which also helps to improve the cycle performance, kinetic performance, etc. of the secondary battery.
[0048] In any embodiment of the present application, the ratio of the air permeability of the first base film to the air permeability of the second base film is greater than 1, and can be optionally 1.05-3.0, and more optionally 1.08-2.0.
[0049] The first base film of the isolation membrane faces the negative electrode and the second base film faces the positive electrode. By adjusting the ratio of the permeability of the first base film and the permeability of the second base film to be greater than 1, the stiffness of the first base film, the second base film and the isolation membrane can be adjusted; in addition, the first base film with greater permeability faces the negative electrode, which can also better alleviate dendrite growth and improve the reliability of the secondary battery.
[0050] In any embodiment of the present application, the air permeability of the first base film is less than or equal to 300s / 100cc, and can be optionally 120-260s / 100cc.
[0051] In any embodiment of the present application, the air permeability of the second base film is less than or equal to 250s / 100cc, and can be optionally 110-220s / 100cc.
[0052] By adjusting the permeability of the first base membrane and / or the permeability of the second base membrane within the above range, the stiffness of the first base membrane, the second base membrane and the isolation membrane can be adjusted, and the isolation membrane can also have good ionic conductivity, which also helps to improve the cycle performance, kinetic performance, etc. of the secondary battery.
[0053] In any embodiment of the present application, the first base film and the second base film each independently include one or more of polyolefins and their derivatives, halogenated polyolefins and their derivatives, polyethers and their derivatives, polyetheretherketones and their derivatives, polyesters and their derivatives, polyimides and their derivatives, and polyvinyl alcohols and their derivatives.
[0054] In any embodiment of the present application, the halogenated polyolefin and its derivatives include one or more of polytetrafluoroethylene and its derivatives, polyvinyl fluoride and its derivatives, polyvinylidene fluoride and its derivatives.
[0055] In any embodiment of the present application, the polyester and its derivatives include one or more of polyethylene terephthalate and its derivatives, polybutylene terephthalate and its derivatives.
[0056] In any embodiment of the present application, the adhesive layer includes a binder. The binder can impart good heat resistance to the separator while ensuring adhesion strength and uniformity between the first base film and the second base film, thereby helping to improve the reliability of the secondary battery.
[0057] In any embodiment of the present application, the adhesive layer includes a binder and a filler. The filler can further improve the heat resistance and physical properties (such as puncture strength) of the separator, thereby helping to enhance the reliability of the secondary battery. In addition, the filler is located between the first base film and the second base film, thereby reducing problems such as powder loss.
[0058] In any embodiment of the present application, the binder includes one or more of polyacrylate, polyacrylic acid, polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-trichloroethylene copolymer, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, carboxymethyl cellulose, hydroxypropyl cellulose, regenerated cellulose, cellulose acetate, cellulose acetate propionate, cellulose acetate butyrate, polyacrylonitrile, polyvinyl alcohol, polyethylene, polypropylene, starch, and cyanoethyl pullulan.
[0059] In any embodiment of the present application, the filler includes at least one of inorganic particles, organic particles, and organic-metal framework materials. Optionally, the inorganic particles include one or more of inorganic particles having a dielectric constant of 5 or greater, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions; optionally, the organic particles include one or more of polycarbonate, polythiophene, polypyridine, polystyrene, polyacrylic wax, polyethylene, polypropylene, cellulose, cellulose modifier, melamine resin, phenolic resin, polyester, silicone resin, polyimide, polyamideimide, polyaromatic amide, polyphenylene sulfide, polysulfone, polyethersulfone, polyetheretherketone, polyaryletherketone, and a copolymer of butyl acrylate and ethyl methacrylate; optionally, the organic-metal framework material includes one or more of a nitrogen-containing heterocyclic ligand building structure, an organic carboxylic acid ligand building structure, and a nitrogen-oxygen mixed ligand building structure.
[0060] In any embodiment of the present application, the thickness of the adhesive layer is greater than or equal to 0.3 μm, and can be optionally 0.5-4 μm. When the thickness of the adhesive layer is within the above range, the separator can have a suitable thickness and can also have good heat resistance and physical strength, thereby improving the reliability of the secondary battery.
[0061] In any embodiment of the present application, the surface density of the adhesive layer is 1.0-6.0 g / m 2 , optional 1.2-5.0g / m 2 .
[0062] In any embodiment of the present application, the bonding strength between the adhesive layer and the first base film is greater than or equal to 3 N / m, and can be optionally 4-15 N / m.
[0063] In any embodiment of the present application, the bonding strength between the adhesive layer and the second base film is greater than or equal to 3 N / m, and can be optionally 4-15 N / m.
[0064] In any embodiment of the present application, the content of the binder is greater than or equal to 10%, and can be optionally 10%-30%, based on the total weight of the adhesive layer.
[0065] In any embodiment of the present application, the content of the filler is less than or equal to 90%, and can be optionally 60%-80%, based on the total weight of the adhesive layer.
[0066] In any embodiment of the present application, the volume distribution particle size Dv50 of the filler is less than or equal to 1.5 μm, and can be optionally 0.1-1.4 μm.
[0067] In any embodiment of the present application, the transverse tensile strength of the isolation film is greater than or equal to 700 kg / cm 2 , can be selected to be greater than or equal to 1000kg / cm 2 .
[0068] In any embodiment of the present application, the longitudinal tensile strength of the isolation film is greater than or equal to 1000 kg / cm 2 , can be selected to be greater than or equal to 1200kg / cm 2 .
[0069] In any embodiment of the present application, the transverse heat shrinkage rate of the isolation film at 250° C. for 1 hour is less than or equal to 5%, and can optionally be less than or equal to 2%.
[0070] In any embodiment of the present application, the longitudinal thermal shrinkage rate of the isolation film at 250° C. for 1 hour is less than or equal to 5%, and can optionally be less than or equal to 2%.
[0071] A second aspect of the present application provides a secondary battery comprising the isolation membrane of the first aspect of the present application.
[0072] In any embodiment of the present application, the secondary battery includes a positive electrode sheet and a negative electrode sheet, the isolation membrane is arranged between the positive electrode sheet and the negative electrode sheet, and the first base membrane of the isolation membrane faces the negative electrode sheet, and the second base membrane of the isolation membrane faces the positive electrode sheet.
[0073] A third aspect of the present application provides an electrical device comprising the secondary battery according to the second aspect of the present application.
[0074] The electric device of the present application includes the secondary battery provided by the present application, and thus has at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] To more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.
[0076] FIG1 is a schematic diagram of an embodiment of a secondary battery provided by the present application.
[0077] FIG2 is an exploded schematic diagram of an embodiment of a secondary battery provided in the present application.
[0078] FIG3 is a schematic diagram of an embodiment of a battery module provided in the present application.
[0079] FIG4 is a schematic diagram of an embodiment of a battery pack provided in the present application.
[0080] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .
[0081] FIG6 is a schematic diagram of an embodiment of an electric device including the secondary battery provided in the present application as a power source.
[0082] In the accompanying drawings, which are not necessarily drawn to scale, the reference numerals are as follows: 1. battery pack; 2. upper housing; 3. lower housing; 4. battery module; 5. secondary battery; 51. housing; 52. electrode assembly; 53. cover plate. DETAILED DESCRIPTION
[0083] Below, the embodiments of the separator, secondary battery, and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially the same structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0084] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0085] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of the present application.
[0086] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of this application.
[0087] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0088] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0089] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0090] Unless otherwise specified, in this application, the terms "first", "second", etc. are used to distinguish different objects rather than to describe a specific order or a primary-secondary relationship.
[0091] In this application, the terms "plurality", "multiple" and the like refer to two or more.
[0092] Unless otherwise specified, the terms used in this application have the common meanings that are commonly understood by those skilled in the art.
[0093] Unless otherwise stated, the numerical values of the various parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise stated, the test temperature of each parameter is 25°C.
[0094] Unless otherwise specified, all ratio parameters involved in this application are compared in the same unit. For example, the thickness of A and B is 1.2:1, in which case the thickness of A and B has the same unit.
[0095] Typically, a secondary battery includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet, and mainly serves to prevent the positive and negative electrodes from short-circuiting.
[0096] The isolation film provided in the embodiments of the present application includes a first base film, a second base film and an adhesive layer, and the adhesive layer is arranged between the first base film and the second base film; the stiffness of the isolation film in the transverse direction (TD) is recorded as T0, and the stiffness of the isolation film in the longitudinal direction (MD) is recorded as M0, then T0 is 1.0-8.0mN×cm, and M0 is 1.2-7.0mN×cm.
[0097] For example, the stiffness T0 in the transverse direction (TD) of the isolation membrane can be 1.0mN×cm, 1.5mN×cm, 1.7mN×cm, 2.0mN×cm, 2.3mN×cm, 2.5mN×cm, 2.8mN×cm, 3.1mN×cm, 3.4mN×cm, 3.7mN×cm, 4.0mN×cm, 4.2mN×cm, 4.5mN×cm, 4.7mN×cm, 4.9mN×cm, 5.0mN×cm, 5.2mN×cm, 5.5mN×cm, 5.8mN×cm, 6.0mN×cm, 6.2mN×cm, 6.5mN×cm, 6.8mN×cm, 7.0mN×cm, 7.5mN×cm, 8.0mN×cm, or a range consisting of any two of the above values.
[0098] The stiffness M0 in the longitudinal (MD) direction of the isolation membrane can be 1.2mN×cm, 1.5mN×cm, 1.8mN×cm, 1.9mN×cm, 2.0mN×cm, 2.2mN×cm, 2.5mN×cm, 2.7mN×cm, 3.0mN×cm, 3.3mN×cm, 3.5mN×cm, 3.8mN×cm, 4.0mN×cm, 4.2mN×cm, 4.5mN×cm, 4.8mN×cm, 5.0mN×cm, 5.2mN×cm, 5.5mN×cm, 5.8mN×cm, 6.0mN×cm, 6.2mN×cm, 6.5mN×cm, 6.8mN×cm, 7.0mN×cm, or a range consisting of any two of the above values.
[0099] The separators currently used in commercial secondary batteries are typically made of polyolefins, such as porous polyethylene or polypropylene membranes. However, these separators have poor heat resistance and experience significant thermal contraction when heated, which can easily lead to direct contact between the positive and negative electrodes of the battery, resulting in internal short circuits and increased safety risks for the secondary battery. To address this issue, the current approach primarily involves coating the polyolefin separator with a heat-resistant inorganic ceramic layer. However, this inorganic ceramic layer has limited effect on improving the separator's overall heat resistance. Furthermore, the inorganic ceramic layer exhibits poor adhesion, making it prone to powder loss and other issues.
[0100] In addition, polyethylene porous membranes, polypropylene porous membranes, etc. are prone to abnormal phenomena such as curling, curling, wrinkling, and stretching during the production, processing, and slitting processes. In addition, it is easy to cause the local size of the finished isolation membrane to be too short, and when used in secondary batteries, it is easy to cause positive and negative electrode short circuit problems, affecting the reliability of the secondary battery.
[0101] Without wishing to be limited to any theory, the inventors have found through extensive research that when the isolation membrane includes a first base membrane, a second base membrane, and an adhesive layer located between the first base membrane and the second base membrane, and the stiffness T0 of the isolation membrane in the transverse direction (TD) is between 1.0 mN×cm and 8.0 mN×cm, and the stiffness M0 of the isolation membrane in the longitudinal direction (MD) is between 1.2 mN×cm and 7.0 mN×cm, the probability of abnormal problems such as curling, curling, wrinkling, and tendon stretching occurring during the production, processing, slitting, and secondary battery preparation of the isolation membrane can be reduced, and the morphology of the isolation membrane can be kept regular, thereby improving the production yield of the secondary battery; in addition, the size of the isolation membrane can be more accurately controlled, reducing the probability of the problem of local size being too short in the processed isolation membrane, thereby reducing the probability of short circuit between the positive and negative electrodes, and reducing the probability of safety accidents such as fire and explosion in the secondary battery, thereby improving the reliability of the secondary battery.
[0102] The embodiments of the present application provide an isolation membrane with a stiffness T0 in the transverse (TD) direction of between 1.0 mN×cm and 8.0 mN×cm, and a stiffness M0 in the longitudinal (MD) direction of between 1.2 mN×cm and 7.0 mN×cm. The isolation membrane can also have good heat resistance and high mechanical strength. When used in a secondary battery, dendrites grown on the negative electrode side are not easy to pierce the isolation membrane. At the same time, the thermal shrinkage rate of the isolation membrane is small, thereby improving the reliability of the secondary battery.
[0103] Therefore, the isolation film provided by the embodiments of the present application can improve the production yield of the secondary battery and can also improve the reliability of the secondary battery.
[0104] The inventors found in their research that when the stiffness T0 of the isolation membrane in the transverse (TD) direction is less than 1.0 mN×cm and / or the stiffness M0 of the isolation membrane in the longitudinal (MD) direction is less than 1.2 mN×cm, abnormal phenomena such as curling, curling, wrinkling, and stretching are likely to occur during the production, processing, slitting, and secondary battery preparation of the isolation membrane, resulting in a low production yield of the secondary battery. At the same time, the prepared isolation membrane has poor heat resistance and is prone to local short size, resulting in a high probability of short circuit between the positive and negative electrodes, affecting the reliability of the secondary battery.
[0105] When the stiffness T0 of the separator in the transverse (TD) direction is greater than 8.0 mN×cm and / or the stiffness M0 of the separator in the longitudinal (MD) direction is greater than 7.0 mN×cm, the separator has excessive stiffness, which results in reduced flexibility, making it difficult to be folded and compressed, and reducing the production yield of the secondary battery. In addition, during the winding and compression process, the first base film and / or the second base film are prone to damage deformation or separation from the adhesive layer, thereby increasing safety risks. In addition, when the stiffness of the separator is too high, its thickness will generally increase. When heated, the degree of thermal shrinkage of the separator's fibers will increase accordingly, ultimately resulting in an increase in the separator's thermal shrinkage rate, an increase in the probability of short circuits between the positive and negative electrodes, and a decrease in the reliability of the secondary battery.
[0106] Optionally, in some embodiments, the stiffness T0 in the transverse direction (TD) of the isolation film can also be 1.5-7.0mN×cm, 1.7-7.0mN×cm, 1.9-7.0mN×cm, 2.0-7.0mN×cm, 1.5-6.0mN×cm, 1.7-6.0mN×cm, 1.9-6.0mN×cm, 2.0-6.0mN×cm, 1.5-5.0mN ×cm, 1.7-5.0mN×cm, 1.9-5.0mN×cm, 2.0-5.0mN×cm, 1.5-4.7mN×cm, 1.7-4.7mN×cm, 1.9-4.7mN×cm, 2.0-4.7mN×cm, 1.5-4.5mN×cm, 1.7-4.5mN×cm, 1.9-4.5mN×cm, 2.0-4.5mN×cm.
[0107] Optionally, in some embodiments, the stiffness M0 in the longitudinal direction (MD) of the isolation film can also be 1.2-6.0 mN×cm, 1.5-6.0 mN×cm, 1.6-6.0 mN×cm, 1.7-6.0 mN×cm, 1.8-6.0 mN×cm, 1.9-6.0 mN×cm, 1.2-5.0 mN×cm, 1.5-5.0 mN×cm, 1.6-5.0 mN×cm m, 1.7-5.0mN×cm, 1.8-5.0mN×cm, 1.9-5.0mN×cm, 1.2-4.0mN×cm, 1.5-4.0mN×cm, 1.6-4.0 mN×cm, 1.7-4.0mN×cm, 1.8-4.0mN×cm, 1.9-4.0mN×cm, 1.2-3.5mN×cm, 1.5-3.5mN×cm, 1.6- 3.5mN×cm, 1.7-3.5mN×cm, 1.8-3.5mN×cm, 1.9-3.5mN×cm, 1.2-3.3mN×cm, 1.5-3.3mN×cm, 1.6-3.3mN×cm, 1.7-3.3mN×cm, 1.8-3.3mN×cm, 1.9-3.3mN×cm.
[0108] This can further improve the heat resistance of the isolation membrane, improve the reliability of the secondary battery, and also improve the production yield of the secondary battery.
[0109] In some embodiments, the ratio of the stiffness T0 of the separator in the transverse direction (TD) to the stiffness M0 of the separator in the longitudinal direction (MD) can be 1.0-2.5, or can be 1.1-2.0, 1.15-2.0, 1.2-2.0, 1.25-2.0, 1.1-1.8, 1.15-1.8, 1.2-1.8, 1.25-1.8, 1.1-1.75, 1.15-1.75, 1.2-1.75, 1.25-1.75, 1.1-1.7, 1.15-1.7, 1.2-1.7, or 1.25-1.7. This can further improve the heat resistance of the separator, the reliability of the secondary battery, and the production yield of the secondary battery.
[0110] In some embodiments, the stiffness of the first base film in the transverse direction (TD) is recorded as T1, and T1 can be 0.25-4.5 mN×cm, for example, it can be 0.25 mN×cm, 0.5 mN×cm, 0.8 mN×cm, 0.9 mN×cm, 1.0 mN×cm, 1.2 mN×cm, 1.5 mN×cm, 1.7 mN×cm, 2.0 mN×cm, 2.2 mN×cm, 2.5 mN×cm, 3.0 mN×cm, 3.5 mN×cm, 4.0 mN×cm, 4.5 mN×cm, or a range consisting of any two of the above values. Optionally, in some embodiments, the stiffness T1 of the first base film in the transverse direction (TD) can also be 0.5-4mN×cm, 0.5-3.5mN×cm, 0.5-3.0mN×cm, 0.5-2.5mN×cm, 0.5-2.0mN×cm, 0.8-4mN×cm, 0.8-3.5mN×cm, 0.8-3.0mN×cm, 0.8-2.5mN×cm, 0.8-2.0mN×cm, 0.9-4mN×cm, 0.9-3.5mN×cm, 0.9-3.0mN×cm, 0.9-2.5mN×cm, 0.9-2.0mN×cm.
[0111] In some embodiments, the stiffness of the first base film in the longitudinal (MD) direction is recorded as M1, and M1 can be 0.15-4.0mN×cm, for example, it can be 0.15mN×cm, 0.3mN×cm, 0.5mN×cm, 0.6mN×cm, 0.75mN×cm, 0.9mN×cm, 1.0mN×cm, 1.1mN×cm, 1.3mN×cm, 1.5mN×cm, 1.8mN×cm, 2.0mN×cm, 2.5mN×cm, 3.0mN×cm, 3.5mN×cm, 4.0mN×cm, or a range consisting of any two of the above values. Optionally, in some embodiments, the stiffness M1 of the first base film in the longitudinal (MD) direction can also be 0.5-3.5mN×cm, 0.5-3.0mN×cm, 0.5-2.5mN×cm, 0.5-2.0mN×cm, 0.5-1.8mN×cm, 0.6-3.5mN×cm, 0.6-3.0mN×cm, 0.6-2.5mN×cm, 0.6-2.0mN×cm, 0.6-1.8mN×cm, 0.75-3.5mN×cm, 0.75-3.0mN×cm, 0.75-2.5mN×cm, 0.75-2.0mN×cm, 0.75-1.8mN×cm.
[0112] In some embodiments, the ratio T1 / M1 of the stiffness T1 in the transverse direction (TD) of the first base film to the stiffness in the longitudinal direction (MD) can be 1.0-3.0, optionally 1.1-2.0, 1.15-2.0, 1.2-2.0, 1.25-2.0, 1.1-1.8, 1.15-1.8, 1.2-1.8, 1.25-1.8, 1.1-1.75, 1.15-1.75, 1.2-1.75, 1.25-1.75, 1.1-1.7, 1.15-1.7, 1.2-1.7, 1.25-1.7.
[0113] By adjusting the stiffness T1 of the first base film in the transverse (TD) direction, the stiffness M1 in the longitudinal (MD) direction and the ratio T1 / M1 of the two within the above range, the heat resistance of the isolation membrane can be further improved, the reliability of the secondary battery can be improved, and the production yield of the secondary battery can also be improved.
[0114] In some embodiments, the stiffness of the second base film in the transverse direction (TD) is recorded as T2, and T2 can be 0.3-5.0 mN×cm, for example, it can be 0.3 mN×cm, 0.5 mN×cm, 0.8 mN×cm, 0.9 mN×cm, 1.1 mN×cm, 1.3 mN×cm, 1.5 mN×cm, 1.8 mN×cm, 2.0 mN×cm, 2.3 mN×cm, 2.5 mN×cm, 2.8 mN×cm, 3.0 mN×cm, 3.5 mN×cm, 4.0 mN×cm, 4.5 mN×cm, 5.0 mN×cm, or a range consisting of any two of the above values. Optionally, in some embodiments, the stiffness T2 of the second base film in the transverse direction (TD) can also be 0.5-4mN×cm, 0.5-3.5mN×cm, 0.5-3.0mN×cm, 0.5-2.5mN×cm, 0.8-4mN×cm, 0.8-3.5mN×cm, 0.8-3.0mN×cm, 0.8-2.5mN×cm, 0.9-4mN×cm, 0.9-3.5mN×cm, 0.9-3.0mN×cm, 0.9-2.5mN×cm.
[0115] In some embodiments, the stiffness of the second base film in the longitudinal (MD) direction is recorded as M2, and M2 can be 0.2-4.5mN×cm, for example, it can be 0.2mN×cm, 0.3mN×cm, 0.5mN×cm, 0.6mN×cm, 0.8mN×cm, 0.9mN×cm, 1.0mN×cm, 1.1mN×cm, 1.2mN×cm, 1.5mN×cm, 1.7mN×cm, 2.1mN×cm, 2.5mN×cm, 3.0mN×cm, 3.5mN×cm, 4.0mN×cm, 4.5mN×cm, or a range consisting of any two of the above values. Optionally, in some embodiments, the stiffness M2 of the second base film in the longitudinal (MD) direction can also be 0.5-4.0mN×cm, 0.5-3.5mN×cm, 0.5-3.0mN×cm, 0.5-2.5mN×cm, 0.5-2.1mN×cm, 0.6-4.0mN×cm, 0.6-3.5mN×cm, 0.6-3.0mN×cm, 0.6-2.5mN×cm, 0.6-2.1mN×cm, 0.8-4.0mN×cm, 0.8-3.5mN×cm, 0.8-3.0mN×cm, 0.8-2.5mN×cm, 0.8-2.1mN×cm.
[0116] In some embodiments, the ratio T2 / M2 of the stiffness of the second base film in the transverse direction (TD) to the stiffness in the longitudinal direction (MD) is 1.0-3.5, and can be optionally 1.1-2.5, 1.15-2.5, 1.2-2.5, 1.22-2.5, 1.1-2.2, 1.15-2.2, 1.2-2.2, 1.22-2.2, 1.1-1.9, 1.15-1.9, 1.2-1.9, 1.22-1.9, 1.1-1.7, 1.15-1.7, 1.2-1.7, 1.22-1.7.
[0117] By adjusting the stiffness T2 of the second base film in the transverse (TD) direction, the stiffness M2 in the longitudinal (MD) direction and the ratio T2 / M2 between the two within the above range, the heat resistance of the isolation membrane can be further improved, the reliability of the secondary battery can be improved, and the production yield of the secondary battery can also be improved.
[0118] The stiffness of the isolation film, the first base film, and the second base film in the transverse (TD) direction and the longitudinal (MD) direction respectively has a well-known meaning in the art and can be measured using known equipment and methods. For example, the test can be performed using the inclined plane method with reference to GB / T18318-2009 and ZB WO 4003-87. The test instrument can be a fully automatic stiffness tester (such as the German DRK309 automatic fabric stiffness tester). During the test, a punching machine can be used to punch out multiple (for example, 12) samples from the isolation film. The sample size can be 25mm×250mm, with the long sides of half of the samples parallel to the transverse (TD) direction of the isolation film, and the long sides of half of the samples parallel to the longitudinal (MD) direction of the isolation film. The angle of the inclined plane can be 41.5°, and the sample advancement speed can be 4mm / s.
[0119] The stiffness of the isolation film in the transverse (TD) direction can be obtained by adjusting one or more parameters such as the stiffness of the first base film in the transverse (TD) direction, the stiffness of the second base film in the transverse (TD) direction, the composition and thickness of the adhesive layer.
[0120] The stiffness of the isolation film in the longitudinal (MD) direction can be obtained by adjusting one or more parameters such as the stiffness of the first base film in the longitudinal (MD) direction, the stiffness of the second base film in the longitudinal (MD) direction, the composition and thickness of the adhesive layer.
[0121] The stiffness of the first base film in the transverse (TD) direction and the longitudinal (MD) direction can be obtained by adjusting the parameters of the first base film (such as one or more of the composition, orientation degree, average fiber diameter, crystallinity, average pore size, thickness, melting point, porosity, air permeability, density, etc.) and / or the preparation process parameters of the first base film (such as one or more of the stretching parameters, heat setting parameters, etc.).
[0122] The stiffness of the second base film in the transverse (TD) and longitudinal (MD) directions can be obtained by adjusting the parameters of the second base film (such as one or more of the composition, orientation degree, average fiber diameter, crystallinity, average pore size, thickness, melting point, porosity, air permeability, density, etc.) and / or the preparation process parameters of the second base film (such as one or more of the stretching parameters, heat setting parameters, etc.).
[0123] In some embodiments, the average fiber filament diameter of the first basement membrane can be 80-300nm, for example, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, 300nm, or a range consisting of any two of the above values. Alternatively, in some embodiments, the average fiber filament diameter of the first basement membrane can also be 80-280nm, 100-280nm, 110-280nm, 130-280nm, 80-260nm, 100-260nm, 110-260nm, 130-260nm, 80-240nm, 100-240nm, 110-240nm, 130-240nm.
[0124] In some embodiments, the average fiber filament diameter of the second basement membrane can be 100-300 nm, for example, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 180 nm, 200 nm, 220 nm, 240 nm, 260 nm, 280 nm, 300 nm, or a range consisting of any two of the above values. Alternatively, in some embodiments, the average fiber filament diameter of the second basement membrane can also be 120-280 nm, 140-280 nm, 100-260 nm, 120-260 nm, 140-260 nm, 100-240 nm, 120-240 nm, 140-240 nm.
[0125] By adjusting the average fiber filament diameter of the first base membrane and / or the average fiber filament diameter of the second base membrane within the above range, the stiffness of the first base membrane, the second base membrane and the isolation membrane can be adjusted, and the isolation membrane can also have good heat resistance and high ionic conductivity, thereby improving the reliability of the secondary battery and the electrochemical properties of the secondary battery, such as cycle performance and kinetic performance.
[0126] The average fiber diameter of the basement membrane (e.g., the first basement membrane, the second basement membrane) has a meaning well known in the art and can be tested using known equipment and methods. For example, a scanning electron microscope (e.g., ZEISS Sigma 300) is used, with reference to JY / T010-1996, to obtain a scanning electron microscope (SEM) image of the basement membrane. Specifically, a test sample of length × width = 5 mm × 5 mm is arbitrarily selected on the basement membrane, and multiple test areas (e.g., 5) are randomly selected in the test sample. The fiber diameter is clearly observed at a certain magnification (e.g., 10K times), and a ruler is used to select multiple positions (e.g., at least 30) for measurement. The average value of the multiple fiber diameters is obtained, which is the average fiber diameter of the basement membrane.
[0127] In some embodiments, the ratio of the crystallinity of the second base film to the crystallinity of the first base film can be greater than 1, for example, it can be 1.03, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, or a range consisting of any two of the above values. Optionally, in some embodiments, the ratio of the crystallinity of the second base film to the crystallinity of the first base film can also be 1.03-1.5, 1.05-1.5, 1.1-1.5, 1.15-1.5, 1.03-1.4, 1.05-1.4, 1.1-1.4, 1.15-1.4, 1.03-1.3, 1.05-1.3, 1.1-1.3, 1.15-1.3, 1.03-1.25, 1.05-1.25, 1.1-1.25, 1.15-1.25.
[0128] The first base film of the isolation membrane faces the negative electrode and the second base film faces the positive electrode. By adjusting the ratio of the crystallinity of the second base film to the crystallinity of the first base film to be greater than 1, the stiffness of the first base film, the second base film and the isolation membrane can be adjusted, which is also beneficial to the preparation of a wound electrode assembly.
[0129] In some embodiments, the crystallinity of the first base film may be 33%-70%, 35%-65%, 35%-60%, 35%-55%, 35%-50%, or 35%-45%.
[0130] In some embodiments, the crystallinity of the second base film may be 35%-80%, optionally 35%-75%, 35%-65%, 35%-55%, 35%-50%, 40%-75%, 40%-65%, 40%-55%.
[0131] By adjusting the crystallinity of the first base film and / or the crystallinity of the second base film within the above range, the stiffness of the first base film, the second base film and the isolation film can be adjusted, and the isolation film can also have good mechanical strength and elasticity, which is beneficial to improving the high temperature resistance and reliability of the secondary battery and is also beneficial to the preparation of a wound electrode assembly.
[0132] The crystallinity of the first and second base films has a well-known meaning in the art and can be measured using known equipment and methods. For example, differential scanning calorimetry can be used for measurement. For details, please refer to GB / T 19466.3-2004. As an example, the measurement can be performed as follows: 4-6 mg of the sample to be tested is placed in the sample chamber of a differential scanning calorimeter. The temperature is increased from 25°C to 350°C at a rate of 10°C / min. The melting endothermic curve of the sample is obtained. The peak area of the curve is calculated relative to the reference value of a 100% crystalline sample to obtain the crystallinity of the sample.
[0133] In some embodiments, the ratio of the thickness of the second base film to the thickness of the first base film may be greater than 1, for example, 1.01, 1.02, 1.05, 1.1, 1.2, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, or a range consisting of any two of the above values. Alternatively, in some embodiments, the ratio of the thickness of the second base film to the thickness of the first base film may also be 1.02-5.0, 1.02-4.0, 1.02-3.0, 1.02-2.5, 1.02-2.0, 1.1-5.0, 1.1-4.0, 1.1-3.0, 1.1-2.5, 1.1-2.0, 1.2-5.0, 1.2-4.0, 1.2-3.0, 1.2-2.5.
[0134] The first base film of the isolation membrane faces the negative electrode and the second base film faces the positive electrode. By adjusting the ratio of the thickness of the second base film to the thickness of the first base film to be greater than 1, the stiffness of the first base film, the second base film and the isolation membrane can be adjusted; in addition, the thickness of the first base film is relatively small, and the stretching ratio during preparation is usually large, so the orientation degree of the first base film is higher and the physical strength (such as puncture strength, etc.) is higher. Therefore, when it faces the negative electrode, it can better alleviate dendrite growth and improve the reliability of the secondary battery.
[0135] In some embodiments, the thickness of the first base film may be less than or equal to 12 μm, for example, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, or a range consisting of any two of the above values. Alternatively, in some embodiments, the thickness of the first base film may be 1.8-12 μm, 1.8-10 μm, 1.8-8 μm, 1.8-7 μm, 1.8-6 μm, 1.8-5 μm, 2-10 μm, 2-8 μm, 2-7 μm, 2-6 μm, 2-5 μm, 2.5-10 μm, 2.5-8 μm, 2.5-7 μm, 2.5-6 μm, 2.5-5 μm.
[0136] In some embodiments, the thickness of the second base film may be less than or equal to 14 μm, and may be 2 μm, 2.5 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or a range consisting of any two of the above values. Alternatively, in some embodiments, the thickness of the second base film may be 2-14 μm, 2-12 μm, 2-10 μm, 2-8 μm, 2-7 μm, 2-6 μm, 3-14 μm, 3-12 μm, 3-10 μm, 3-8 μm, 3-7 μm, or 3-6 μm.
[0137] By adjusting the thickness of the first base film and / or the thickness of the second base film within the above range, the stiffness of the first base film, the second base film and the separator can be adjusted, which is also beneficial for the secondary battery to have a high energy density.
[0138] The thickness of the first base film and the second base film has a well-known meaning in the art and can be measured using known equipment and methods. For example, six sets of parallel samples can be taken and the thickness of each set of samples can be measured at different locations using a micrometer thickness gauge. At least 20 locations are measured for each set of samples, and the average thickness of the six sets of samples is taken as the sample thickness.
[0139] In some embodiments, the ratio of the melting point of the first base film to the melting point of the second base film can be less than 1, for example, it can be 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.82, 0.85, 0.9, 0.92, 0.95, or a range consisting of any two of the above values. Optionally, in some embodiments, the ratio of the melting point of the first base film to the melting point of the second base film can also be 0.2-0.95, 0.25-0.95, 0.3-0.95, 0.35-0.95, 0.4-0.95, 0.2-0.92, 0.25-0.92, 0.3-0.92, 0.35-0.92, 0.4-0.92, 0.2-0.90, 0.25-0.90, 0.3-0.90, 0.35-0.90, 0.4-0.90, 0.2-0.85, 0.25-0.85, 0.3-0.85, 0.35-0.85, 0.4-0.85.
[0140] The first base film of the isolation membrane faces the negative electrode and the second base film faces the positive electrode. By adjusting the ratio of the melting point of the first base film and the melting point of the second base film to be less than 1, the stiffness of the first base film, the second base film and the isolation membrane can be adjusted; in addition, the melting point of the first base film is low and the physical strength (such as puncture strength) is high, so when it faces the negative electrode, it can better alleviate dendrite growth and improve the reliability of the secondary battery.
[0141] In some embodiments, the melting point of the first base film may be greater than or equal to 110°C, for example, it may be 110°C, 115°C, 120°C, 130°C, 135°C, 140°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, or a range consisting of any two of the above values. Optionally, in some embodiments, the melting point of the first base film can also be 120℃-180℃, 120℃-170℃, 120℃-165℃, 120℃-160℃, 120℃-155℃, 120℃-150℃, 125℃-180℃, 125℃-170℃, 125℃-165℃, 125℃-160℃, 125℃-155℃, 125℃-150℃, 135℃-180℃, 135℃-170℃, 135℃-165℃, 135℃-160℃, 135℃-155℃, 135℃-150℃.
[0142] In some embodiments, the melting point of the second base film may be greater than or equal to 150°C, for example, 150°C, 160°C, 165°C, 170°C, 180°C, 190°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 330°C, 350°C, or a range consisting of any two of the above values. Alternatively, in some embodiments, the melting point of the second base film may be 165°C-330°C, 165°C-320°C, 165°C-300°C, 165°C-280°C, 170°C-330°C, 170°C-320°C, 170°C-300°C, 170°C-280°C, 180°C-330°C, 180°C-320°C, 180°C-300°C, 180°C-280°C.
[0143] By adjusting the melting point of the first base film and / or the melting point of the second base film within the above range, the stiffness of the first base film, the second base film and the isolation film can be adjusted, and the isolation film can also have good closed-cell properties, which is beneficial to improving the reliability of the secondary battery.
[0144] The melting points of the first and second base films are well known in the art and can be measured using known equipment and methods. For example, differential scanning calorimetry can be used for measurement. For details, please refer to GB / T 19466.3-2004. As an example, the measurement can be performed as follows: 4-6 mg of the sample to be tested is placed in the sample chamber of a differential scanning calorimeter. The temperature is raised from 25°C to 400°C at a rate of 10°C / min. The melting endothermic curve of the sample is obtained, and the temperature corresponding to the peak of the curve is the melting point of the sample.
[0145] In some embodiments, the ratio of the average pore size of the second base membrane to the average pore size of the first base membrane may be greater than 1, for example, 1.05, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.8, 2.0, 2.2, 2.5, 2.8, or a range consisting of any two of the above values. Alternatively, in some embodiments, the ratio of the average pore size of the second base membrane to the average pore size of the first base membrane may also be 1.05-2.5, 1.05-2.2, 1.05-2, 1.05-1.8, 1.05-1.5, 1.1-2.5, 1.1-2.2, 1.1-2, 1.1-1.8, 1.1-1.5, 1.2-2.5, 1.2-2.2, 1.2-2, 1.2-1.8.
[0146] The first base membrane of the isolation membrane faces the negative electrode and the second base membrane faces the positive electrode. By adjusting the ratio of the average pore size of the second base membrane to the average pore size of the first base membrane to be greater than 1, the stiffness of the first base membrane, the second base membrane and the isolation membrane can be adjusted; in addition, the first base membrane with a smaller average pore size faces the negative electrode, which can better alleviate the growth of dendrites and better homogenize the ion flow from the positive electrode, thereby reducing the problems of rapid dendrite growth and overly sharp dendrite morphology due to excessive ion concentration in local positions of the negative electrode, and also helps to improve the cycle performance and kinetic performance of the secondary battery.
[0147] In some embodiments, the average pore size of the first basement membrane can be 48-1800nm, for example, it can be 48nm, 55nm, 60nm, 80nm, 90nm, 100nm, 150nm, 180nm, 200nm, 220nm, 250nm, 300nm, 350nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1200nm, 1400nm, 1600nm, 1800nm, or a range consisting of any two of the above values. Optionally, in some embodiments, the average pore size of the first basement membrane can also be 50-1400nm, 60-1400nm, 70-1400nm, 80-1400nm, 50-1000nm, 60-1000nm, 70-1000nm, 80-1000nm, 50-600nm, 60-600nm, 70-600nm, 80-600nm, 50-300nm, 60-300nm, 70-300nm, 80-300nm, 50-200nm, 60-200nm, 70-200nm, 80-200nm.
[0148] In some embodiments, the average pore size of the second basement membrane can be 50-2000nm, for example, it can be 50nm, 60nm, 80nm, 90nm, 100nm, 150nm, 180nm, 200nm, 220nm, 250nm, 300nm, 350nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1200nm, 1400nm, 1600nm, 1800nm, 2000nm, or a range consisting of any two of the above values. Optionally, in some embodiments, the average pore size of the second basement membrane can also be 60-1600nm, 80-1600nm, 100-1600nm, 120-1600nm, 60-1200nm, 80-1200nm, 100-1200nm, 120-1200nm, 60-800nm, 80-800nm, 100-800nm, 120-800nm, 60-400nm, 80-400nm, 100-400nm, 120-400nm, 60-300nm, 80-300nm, 100-300nm, 120-300nm.
[0149] By adjusting the average pore size of the first base membrane and / or the average pore size of the second base membrane within the above range, the stiffness of the first base membrane, the second base membrane and the isolation membrane can be adjusted; the first base membrane and the second base membrane can also better alleviate the growth of dendrites and improve the reliability of the secondary battery; the isolation membrane can also have good ionic conductivity, which also helps to improve the cycle performance, kinetic performance, etc. of the secondary battery.
[0150] The average pore size of the first base film and the second base film has a well-known meaning in the art and can be measured using known equipment and methods. For example, the test can be performed using a mercury porosimeter with reference to GB / T 21650.1-2008.
[0151] In some embodiments, the ratio of the porosity of the second basement membrane to the porosity of the first basement membrane can be greater than 1, for example, it can be 1.01, 1.05, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, or a range consisting of any two of the above values. Optionally, in some embodiments, the ratio of the porosity of the second basement membrane to the porosity of the first basement membrane can also be 1.01-2.8, 1.05-2.8, 1.1-2.8, 1.2-2.8, 1.3-2.8, 1.01-2.4, 1.05-2.4, 1.1-2.4, 1.2-2.4, 1.3-2.4, 1.01-2.0, 1.05-2.0, 1.1-2.0, 1.2-2.0, 1.3-2.0.
[0152] The first base film of the isolation membrane faces the negative electrode and the second base film faces the positive electrode. By adjusting the ratio of the porosity of the second base film to the porosity of the first base film to be greater than 1, the stiffness of the first base film, the second base film and the isolation membrane can be adjusted; in addition, the first base film with smaller porosity faces the negative electrode, which can also better alleviate dendrite growth and improve the reliability of the secondary battery.
[0153] In some embodiments, the porosity of the first base film is 28%-70%, for example, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 65%, 70%, or a range consisting of any two of the above values. Alternatively, in some embodiments, the porosity of the first base film may also be 30%-70%, 30%-60%, 30%-55%, 30%-52%, 30%-50%, 32%-70%, 32%-60%, 32%-55%, 32%-52%, or 32%-50%.
[0154] In some embodiments, the porosity of the second base film may be 30%-80%, for example, 30%, 33%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, or a range consisting of any two of the above values. Alternatively, in some embodiments, the porosity of the second base film may also be 33%-80%, 33%-75%, 33%-70%, 33%-65%, 33%-60%, 33%-55%, 35%-80%, 35%-75%, 35%-70%, 35%-65%, 35%-60%, 35%-55%.
[0155] By adjusting the porosity of the first base membrane and / or the porosity of the second base membrane within the above range, the stiffness of the first base membrane, the second base membrane and the isolation membrane can be adjusted, and the isolation membrane can also have good ionic conductivity, which also helps to improve the cycle performance, kinetic performance, etc. of the secondary battery.
[0156] In some embodiments, the porosity of the isolation membrane may be 27%-65%, and optionally 33%-55%.
[0157] The porosity of the isolation film, the first base film, and the second base film has a well-known meaning in the art and can be measured using known equipment and methods. For example, the porosity can be measured using a mercury intrusion porosimeter according to GB / T 21650.1-2008.
[0158] In some embodiments, the ratio of the air permeability of the first base film to the air permeability of the second base film can be greater than 1, for example, it can be 1.05, 1.08, 1.1, 1.15, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, or a range consisting of any two of the above values. Optionally, in some embodiments, the ratio of the air permeability of the first base film to the air permeability of the second base film can also be 1.05-3.0, 1.05-2.6, 1.05-2.4, 1.05-2.2, 1.05-2.0, 1.08-3.0, 1.08-2.6, 1.08-2.4, 1.08-2.2, 1.08-2.0, 1.1-3.0, 1.1-2.6, 1.1-2.4, 1.1-2.2, 1.1-2.0, 1.2-3.0, 1.2-2.6, 1.2-2.4, 1.2-2.2, 1.2-2.0.
[0159] The first base film of the isolation membrane faces the negative electrode and the second base film faces the positive electrode. By adjusting the ratio of the permeability of the first base film and the permeability of the second base film to be greater than 1, the stiffness of the first base film, the second base film and the isolation membrane can be adjusted; in addition, the first base film with greater permeability faces the negative electrode, which can also better alleviate dendrite growth and improve the reliability of the secondary battery.
[0160] In some embodiments, the air permeability of the first base film may be less than or equal to 300s / 100cc, for example, it may be 110s / 100cc, 120s / 100cc, 140s / 100cc, 160s / 100cc, 180s / 100cc, 200s / 100cc, 220s / 100cc, 240s / 100cc, 260s / 100cc, 280s / 100cc, 300s / 100cc, or a range consisting of any two of the above values. Optionally, in some embodiments, the air permeability of the first base film may be 110-300s / 100cc, 110-280s / 100cc, 110-260s / 100cc, 110-240s / 100cc, 120-300s / 100cc, 120-280s / 100cc, 120-260s / 100cc, 120-240s / 100cc.
[0161] In some embodiments, the air permeability of the second base film can be less than or equal to 250s / 100cc, for example, it can be 100s / 100cc, 110s / 100cc, 120s / 100cc, 140s / 100cc, 160s / 100cc, 180s / 100cc, 200s / 100cc, 220s / 100cc, 230s / 100cc, 250s / 100cc, or a range consisting of any two of the above values. Optionally, in some embodiments, the air permeability of the second base film can also be 100-250s / 100cc, 100-230s / 100cc, 100-220s / 100cc, 100-200s / 100cc, 110-230s / 100cc, 110-220s / 100cc, 110-200s / 100cc.
[0162] By adjusting the permeability of the first base membrane and / or the permeability of the second base membrane within the above range, the stiffness of the first base membrane, the second base membrane and the isolation membrane can be adjusted, and the isolation membrane can also have good ionic conductivity, which also helps to improve the cycle performance, kinetic performance, etc. of the secondary battery.
[0163] The air permeability of the separator, first base film, and second base film is well known in the art and can be measured using known equipment and methods. For example, the test can be performed in accordance with GB / T 36363-2018. The test gas can be 100cc of air.
[0164] The term "air permeability" refers to the test result of the air permeability of the film. The greater the air permeability of the film, the worse the air permeability.
[0165] In some embodiments, the first base film and the second base film may each independently include one or more of polyolefins and their derivatives, halogenated polyolefins and their derivatives, polyethers and their derivatives, polyetheretherketones and their derivatives, polyesters and their derivatives, polyimides (PI) and their derivatives, and polyvinyl alcohol and its derivatives.
[0166] Alternatively, the polyolefin and its derivatives may include one or more of polyethylene (PE) and its derivatives, polypropylene (PP) and its derivatives.
[0167] Alternatively, the halogenated polyolefin and its derivatives may include one or more of polytetrafluoroethylene (PTFE) and its derivatives, polyvinyl fluoride and its derivatives, and polyvinylidene fluoride and its derivatives.
[0168] Alternatively, the polyester and its derivatives may include one or more of polyethylene terephthalate (PET) and its derivatives, polybutylene terephthalate (PBT) and its derivatives.
[0169] Derivatives usually refer to products derived from polymers in which hydrogen atoms or atomic groups are replaced by other atoms or atomic groups.
[0170] In some embodiments, the adhesive layer includes a binder, which can impart good heat resistance to the separator while ensuring adhesion strength and uniformity between the first base film and the second base film, thereby helping to improve the reliability of the secondary battery.
[0171] In some embodiments, the binder may include one or more of polyacrylate, polyacrylic acid, polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-trichloroethylene copolymer, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, carboxymethyl cellulose, hydroxypropyl cellulose, regenerated cellulose, cellulose acetate, cellulose acetate propionate, cellulose acetate butyrate, polyacrylonitrile, polyvinyl alcohol, polyethylene, polypropylene, starch, and cyanoethyl pullulan.
[0172] In some embodiments, the adhesive layer may include a binder and a filler. The filler can further improve the heat resistance and physical properties (such as puncture strength) of the separator, thereby helping to enhance the reliability of the secondary battery. Furthermore, the filler is located between the first and second base films, thereby reducing problems such as powder loss.
[0173] As an example, in some embodiments, the filler may include at least one of inorganic particles, organic particles, and an organic-metal framework material.
[0174] Alternatively, the inorganic particles may include one or more of inorganic particles having a dielectric constant of 5 or greater, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.
[0175] Alternatively, the inorganic particles having a dielectric constant of 5 or more may include boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviated as PLZT, 0<m<1, 0<n<1), Pb(Mg3Nb 2 / 3 )O3-PbTiO3 (abbreviated as PMN-PT), and at least one of their respective modified inorganic particles. Optionally, the modification method of each inorganic particle may be chemical modification and / or physical modification. The chemical modification method includes coupling agent modification (for example, using silane coupling agent, titanate coupling agent, etc.), surfactant modification, polymer grafting modification, etc. The physical modification method may be mechanical force dispersion, ultrasonic dispersion, high energy treatment, etc. The modification treatment can reduce the agglomeration of inorganic particles, thereby enabling the adhesive layer to have a more stable and uniform structure; in addition, by selecting a coupling agent, surfactant or polymer with a specific functional group to modify the inorganic particles, it is also helpful to improve the wetting and retention properties of the adhesive layer to the electrolyte, and improve the adhesion of the adhesive layer to the first base film and the second base film.
[0176] Alternatively, the inorganic particles having ion conductivity but not storing ions may include Li3PO4, lithium titanium phosphate Li x1 Ti y1 (PO4)3, lithium aluminum titanium phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum lithium titanate Li x4 La y4 TiO3, lithium germanium thiophosphate Li x5 Ge y5 P z2 S w , lithium nitride Li x6 N y6 、SiS2 type glass Li x7 Siy7 S z3 and P2S5 glass Li x8 P y8 S z4 At least one of the following: 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7. This can further improve the ion conductivity of the isolation membrane.
[0177] Alternatively, the inorganic particles capable of undergoing electrochemical reaction may include at least one of lithium-containing transition metal oxides, lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials, and lithium-titanium compounds.
[0178] Alternatively, the organic particles may include one or more of polycarbonate, polythiophene, polypyridine, polystyrene, polyacrylic wax, polyethylene, polypropylene, cellulose, a cellulose modifier (e.g., carboxymethyl cellulose), a melamine resin, a phenolic resin, a polyester (e.g., polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate), a silicone resin, a polyimide, a polyamideimide, a polyaromatic amide, polyphenylene sulfide, a polysulfone, a polyethersulfone, a polyetheretherketone, a polyaryletherketone, a copolymer of butyl acrylate and ethyl methacrylate (e.g., a cross-linked polymer of butyl acrylate and ethyl methacrylate).
[0179] Optionally, the organic-metal framework material may include one or more of a nitrogen-containing heterocyclic ligand building structure, an organic carboxylic acid ligand building structure, and a nitrogen-oxygen mixed ligand building structure.
[0180] In some embodiments, the content of the binder may be greater than or equal to 10%, optionally 10%-30%, based on the total weight of the adhesive layer.
[0181] In some embodiments, the content of the filler may be less than or equal to 90%, optionally 40%-90%, 60%-80%, based on the total weight of the adhesive layer.
[0182] In some embodiments, the adhesive layer may further include a dispersant, such as carboxymethyl cellulose, to adjust the viscosity of the adhesive layer slurry and improve the quality and uniformity of the adhesive layer.
[0183] In some embodiments, the content of the dispersant may be less than or equal to 25%, optionally less than or equal to 20%, based on the total weight of the adhesive layer.
[0184] In some embodiments, the thickness of the adhesive layer can be greater than or equal to 0.3 μm, and can be optionally 0.5-4 μm. When the thickness of the adhesive layer is within the above range, the separator can have a suitable thickness and can also have good heat resistance and physical strength, thereby improving the reliability of the secondary battery.
[0185] The test method for the thickness of the adhesive layer may refer to the test method for the thickness of the first base film and the second base film.
[0186] In some embodiments, the surface density of the adhesive layer can be 1.0-6.0 g / m 2 , optional 1.2-5.0g / m 2 .
[0187] In some embodiments, the bonding strength between the adhesive layer and the first base film may be greater than or equal to 3 N / m, and may be 4-15 N / m.
[0188] In some embodiments, the bonding strength between the adhesive layer and the second base film may be greater than or equal to 3 N / m, and may be 4-15 N / m.
[0189] This can prevent the adhesive layer from being separated from the first base film and the second base film, thereby helping to improve the reliability of the secondary battery.
[0190] In some embodiments, the volume distribution particle size Dv50 of the filler may be less than or equal to 1.5 μm, and may be optionally 0.1-1.4 μm, 0.15-1.0 μm, 0.2-0.8 nm, or 0.3-0.7 nm.
[0191] In some embodiments, the transverse direction (TD) tensile strength of the separator may be greater than or equal to 700 kg / cm 2 , can be selected to be greater than or equal to 1000kg / cm 2 .
[0192] In some embodiments, the longitudinal tensile strength of the separator may be greater than or equal to 1000 kg / cm 2 , can be selected to be greater than or equal to 1200kg / cm 2 .
[0193] In some embodiments, the transverse direction (TD) thermal shrinkage of the isolation film at 250° C. for 1 hour may be less than or equal to 5%, and optionally less than or equal to 2%.
[0194] In some embodiments, the longitudinal (MD) thermal shrinkage of the isolation film at 250° C. for 1 hour may be less than or equal to 5%, and optionally less than or equal to 2%.
[0195] When at least one of the transverse tensile strength, longitudinal tensile strength, transverse thermal shrinkage, and longitudinal thermal shrinkage of the separator meets the given range, the separator can have good heat resistance and physical strength, thereby helping to improve the reliability of the secondary battery.
[0196] The transverse tensile strength, longitudinal tensile strength, transverse thermal shrinkage, and longitudinal thermal shrinkage of the separator are all well-known in the art and can be measured using known equipment and methods. For example, they can all be tested in accordance with GB / T 36363-2018.
[0197] [Preparation method]
[0198] The embodiments of the present application also provide a method for preparing the isolation film provided in the embodiments of the present application.
[0199] The method comprises the following steps: providing a first base film and a second base film; providing an adhesive layer slurry, wherein the adhesive layer slurry comprises a binder; coating the adhesive layer slurry on the first base film and / or the second base film; and compounding the first base film and the second base film to obtain an isolation film.
[0200] The first base film and the second base film are compounded by an adhesive layer slurry, which is a simple process and can further improve the heat resistance and physical strength of the isolation membrane, thereby helping to improve the reliability of the secondary battery. The first base film and the second base film are compounded by an adhesive layer slurry, which can also avoid process defects in the process of directly hot pressing the first base film and the second base film. In the process of directly hot pressing the first base film and the second base film, the applied force is usually at the MPa level; in addition, if the applied temperature is too high, the porosity of the isolation membrane will become smaller and the air permeability will become worse; if the applied temperature is too low, the first base film and the second base film will not be firmly bonded, so it is necessary to select a suitable hot pressing temperature, which makes the direct hot pressing conditions more stringent.
[0201] In some embodiments, the bonding layer slurry may further include a filler. Optionally, the filler may include at least one of inorganic particles, organic particles, and an organic-metal framework material.
[0202] In some embodiments, the solid content of the bonding layer slurry may be 35%-50%.
[0203] In some embodiments, the viscosity of the bonding layer slurry may be 250-380 mPa.s.
[0204] In some embodiments, the coating speed of the bonding layer slurry may be greater than 50 m / min.
[0205] In some embodiments, the method of providing the first base film or the second base film may include commercial purchase.
[0206] In some embodiments, the method for providing a first base film may include the steps of: providing raw materials for forming the first base film, melt-extruding, stretching, and heat-setting the raw materials to obtain the first base film.
[0207] In some embodiments, in the step of providing the first base film, the machine direction (MD) stretching ratio may be 8-12 times.
[0208] In some embodiments, in the step of providing the first base film, the transverse direction (TD) stretching ratio may be 2-6 times.
[0209] In some embodiments, in the step of providing the first base film, the heat setting temperature may be 100°C-160°C.
[0210] In some embodiments, in the step of providing the first base film, the heat setting time may be 20-60 seconds.
[0211] By adjusting the preparation parameters of the first base film, such as stretching parameters, heat setting parameters, etc., the stiffness of the first base film can be adjusted.
[0212] In some embodiments, the method for providing a second base film may include the steps of: providing raw materials for forming the second base film, melt-extruding, stretching, and heat-setting the raw materials to obtain the second base film.
[0213] In some embodiments, in the step of providing the second base film, the machine direction (MD) stretching ratio may be 5-15 times.
[0214] In some embodiments, in the step of providing the second base film, the film may be stretched in the transverse direction (TD) or not. When the film is stretched in the transverse direction (TD), the stretching ratio may be 1.5-6 times.
[0215] In some embodiments, in the step of providing the second base film, the heat setting temperature may be 80°C-130°C.
[0216] In some embodiments, in the step of providing the second base film, the heat setting time may be 30-60 seconds.
[0217] By adjusting the preparation parameters of the second base film, such as stretching parameters, heat setting parameters, etc., the stiffness of the second base film can be adjusted.
[0218] In some embodiments, the adhesive layer slurry may be coated by transfer coating, spin coating, dip coating, etc., which is not limited in the embodiments of the present application.
[0219] Unless otherwise specified, all raw materials used in the method for preparing the separator (eg, the first base film, the second base film, the adhesive, the filler, etc.) can be purchased commercially.
[0220] secondary batteries
[0221] An embodiment of the present application also provides a secondary battery.
[0222] Secondary batteries, also known as rechargeable batteries or storage batteries, are batteries that can be recharged after discharge to reactivate the active materials and continue to be used. Typically, a secondary battery consists of an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator is placed between the positive and negative electrodes to prevent short circuits between the positive and negative electrodes while allowing active ions to pass through.
[0223] The present application has no particular restrictions on the type of secondary battery. For example, the secondary battery can be a lithium ion battery, a sodium ion battery, a lithium metal battery, a sodium metal battery, a lithium-air battery, a sodium-air battery, a lithium-sulfur battery, a sodium-sulfur battery, etc. In particular, the secondary battery can be a lithium ion battery or a sodium ion battery.
[0224] The secondary battery provided in the embodiments of the present application includes the isolation membrane described above or the isolation membrane prepared by the method described above. The isolation membrane can improve the production yield of the secondary battery and also improve the reliability of the secondary battery.
[0225] In some embodiments, the secondary battery includes a positive electrode sheet and a negative electrode sheet, and the separator is disposed between the positive electrode sheet and the negative electrode sheet, and the first base film of the separator is oriented toward (ie, close to) the negative electrode sheet, and the second base film of the separator is oriented toward (ie, close to) the positive electrode sheet.
[0226] [Positive electrode]
[0227] The composition and structure of the positive electrode plate can be selected according to the type of secondary battery, and the embodiments of the present application are not limited thereto.
[0228] In some embodiments, the positive electrode sheet may include a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector and comprising a positive electrode active material. For example, the positive electrode current collector may have two opposing surfaces in its thickness direction, and the positive electrode film layer may be disposed on either or both of the two opposing surfaces of the positive electrode current collector.
[0229] The type of the positive electrode active material may be selected according to the type of the secondary battery, and the embodiments of the present application are not limited thereto.
[0230] For example, when the secondary battery is a lithium-ion battery, the positive electrode active material may include, but is not limited to, at least one of a lithium transition metal oxide, a lithium-containing phosphate, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.
[0231] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium ion battery may include a general formula of Li a Ni b Co c M d O e A f At least one of a lithium transition metal oxide and a modified compound thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M includes at least one of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A includes at least one of N, F, S and Cl.
[0232] As an example, the positive active material for lithium ion batteries may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523),LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 At least one of O2, LiFePO4, and LiMnPO4.
[0233] For example, when the secondary battery is a sodium ion battery, the positive electrode active material may include but is not limited to at least one of sodium-containing transition metal oxides, polyanion materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian blue materials.
[0234] As an example, the positive active material for sodium ion batteries may include NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, NaNi 1 / 2 Ti 1 / 2 O2、NaNi 1 / 2 Mn 1 / 2 O2、Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2、NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, Prussian blue materials, general formula X p M' q (PO4) r O x Y 3-x At least one of the materials. p M' q (PO4) r O x Y 3-x , 0<p≤4, 0<q≤2, 1≤r≤3, 0≤x≤2, X includes H + 、Li + 、Na + , K + and NH4 + At least one of, M' comprises a transition metal cation, optionally comprising at least one of V, Ti, Mn, Fe, Co, Ni, Cu and Zn, and Y comprises a halogen anion, optionally comprising at least one of F, Cl and Br.
[0235] The modified compounds of the above-mentioned positive electrode active materials may be used to perform doping modification and / or surface coating modification on the positive electrode active materials.
[0236] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. The present application does not particularly limit the type of the positive electrode conductive agent. For example, the positive electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0237] In some embodiments, the positive electrode film layer may further optionally include a positive electrode binder. This application does not particularly limit the type of positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic resin.
[0238] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of aluminum, an aluminum alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0239] The positive electrode film is typically formed by coating a positive electrode slurry onto a positive electrode current collector, drying it, and cold pressing it. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).
[0240] [Negative electrode]
[0241] The composition and structure of the negative electrode plate can be selected according to the type of secondary battery, and the embodiments of the present application are not limited thereto.
[0242] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and comprising a negative electrode active material. For example, the negative electrode current collector may have two opposing surfaces in its thickness direction, and the negative electrode film layer may be disposed on either or both of the two opposing surfaces of the negative electrode current collector.
[0243] The negative electrode active material may be any negative electrode active material known in the art for use in secondary batteries. For example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. Silicon-based materials may include at least one of elemental silicon, silicon oxide, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include at least one of elemental tin, tin oxide, and tin alloys.
[0244] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. The present application does not particularly limit the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0245] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. The present application does not particularly limit the type of the negative electrode binder. As examples, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0246] In some embodiments, the negative electrode film layer may further include other additives, such as thickeners, sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like.
[0247] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, a copper alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0248] The negative electrode film layer is typically formed by coating the negative electrode slurry onto the negative electrode current collector, drying it, and cold pressing it. The negative electrode slurry is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring them uniformly. The solvent can be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.
[0249] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some embodiments, the negative electrode plate of the present application also includes a protective layer covering the surface of the negative electrode film layer.
[0250] [Electrolyte]
[0251] During the charge and discharge process of a secondary battery, active ions are embedded and released back and forth between the positive and negative electrodes, and the electrolyte conducts the active ions between the positive and negative electrodes. This application does not specifically limit the type of electrolyte, and the electrolyte can be selected according to actual needs.
[0252] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not particularly limited and can be selected according to actual needs.
[0253] For example, when the secondary battery is a lithium ion battery, the electrolyte salt may include, as an example, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0254] For example, when the secondary battery is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bisfluorosulfonyl imide (NaFSI), sodium bistrifluoromethanesulfonyl imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobisoxalatophosphate (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).
[0255] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), and diethyl sulfone (ESE).
[0256] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.
[0257] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet can be made into an electrode assembly through a winding process and / or a lamination process.
[0258] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0259] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0260] The present application has no particular limitation on the shape of the secondary battery, which can be cylindrical, square, or any other shape. FIG1 shows a secondary battery 5 with a square structure as an example.
[0261] In some embodiments, as shown in FIG2 , the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can be formed into an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.
[0262] Methods for preparing secondary batteries are well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte can be assembled to form a secondary battery. For example, the positive electrode sheet, separator, and negative electrode sheet can be wound and / or laminated to form an electrode assembly. The electrode assembly is then placed in an outer package, dried, and then injected with electrolyte. The secondary battery is then vacuum packaged, allowed to stand, formed, and shaped.
[0263] In some embodiments, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0264] Figure 3 is a schematic diagram of an exemplary battery module 4. As shown in Figure 3 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured using fasteners.
[0265] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0266] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0267] Figures 4 and 5 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 4 and 5, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0268] Electrical devices
[0269] The embodiments of the present application also provide an electrical device, which includes at least one of the secondary batteries, battery modules, or battery packs provided in the embodiments of the present application. The secondary batteries, battery modules, or battery packs can be used as power sources for the electrical device, or as energy storage units for the electrical device. The electrical device can be, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0270] The electrical device can select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0271] Figure 6 is a schematic diagram of an exemplary electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of this device, a battery pack or battery module may be used.
[0272] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a secondary battery as a power source.
[0273] Example
[0274] The following examples describe the present disclosure in more detail. These examples are intended to be illustrative only, as various modifications and variations within the scope of the present disclosure will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing. The instruments used in the examples are commercially available.
[0275] The secondary batteries of Examples 1-12 and Comparative Examples 1-3 were all prepared according to the following method.
[0276] Preparation of isolation membrane
[0277] A first base film and a second base film are provided. Parameters of the first base film and the second base film are shown in Table 1.
[0278] Providing an adhesive layer slurry: boehmite, polyacrylate, and carboxymethyl cellulose are uniformly mixed in an appropriate amount of deionized water as a solvent in a mass ratio of 4:1:1 to prepare an adhesive layer slurry.
[0279] The adhesive layer slurry is coated on the first base film through a coating machine. Another unwinding roller is used for the second base film, which is laminated to the adhesive layer slurry surface of the first base film. The oven temperature is controlled at 40°C, dried for 5 seconds, and pressed at a pressure of 10N to obtain an isolation film.
[0280] Preparation of positive electrode
[0281] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed evenly in an appropriate amount of solvent N-methylpyrrolidone (NMP) in a mass ratio of 96.2:2.7:1.1 to obtain a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through drying, cold pressing, slitting, cutting and other processes.
[0282] Preparation of negative electrode sheet
[0283] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) are mixed evenly in an appropriate amount of solvent deionized water according to a mass ratio of 96.4:0.7:1.8:1.1 to obtain a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through the processes of drying, cold pressing, slitting and cutting.
[0284] Preparation of electrolyte
[0285] Ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:30:40 to obtain an organic solvent, and fully dried LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0286] Preparation of secondary batteries
[0287] The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in sequence to obtain an electrode assembly; the electrode assembly is placed in an outer package, dried, and then injected with electrolyte. After vacuum packaging, standing, formation, shaping and other processes, a secondary battery is obtained.
[0288] In the above-described embodiments and comparative examples, the stiffness of the separator, first base film, and second base film in the transverse (TD) and longitudinal (MD) directions can be tested using the inclined plane method in accordance with GB / T 18318-2009 and ZB WO 4003-87. The testing instrument can be a fully automatic stiffness tester (such as the German DRK309 automatic fabric stiffness tester). During testing, a punch press can be used to punch out multiple (e.g., 12) specimens from the separator. The specimen dimensions can be 25 mm x 250 mm, with the long sides of half the specimens parallel to the transverse (TD) direction of the separator, and the long sides of the other half parallel to the longitudinal (MD) direction of the separator. The inclined plane angle can be 41.5°, and the specimen advancement speed can be 4 mm / s.
[0289] In Table 1, the stiffness of the isolation membrane in the transverse (TD) direction is recorded as T0, the stiffness of the isolation membrane in the longitudinal (MD) direction is recorded as M0, the stiffness of the first base membrane in the transverse (TD) direction is recorded as T1, the stiffness of the first base membrane in the longitudinal (MD) direction is recorded as M1, the stiffness of the second base membrane in the transverse (TD) direction is recorded as T2, and the stiffness of the second base membrane in the longitudinal (MD) direction is recorded as M2.
[0290] Test section
[0291] (1) Thermal shrinkage test of isolation film
[0292] Sample preparation: The isolation film prepared above was punched out into samples with a width of 50 mm and a length of 100 mm using a punching machine. Five parallel samples were placed on a glass plate and fixed.
[0293] Sample test: The temperature of the blast oven is set to 250°C. After the temperature reaches the set temperature and stabilizes for 60 minutes, the glass plate is placed in the blast oven and the time is set for 1 hour. After the time is up, the width of the isolation film is measured and the value is marked as a.
[0294] Calculation of thermal shrinkage: Transverse direction (TD) thermal shrinkage = [(50-a) / 50] × 100%, and the average value of 5 parallel samples is taken as the test result.
[0295] (2) Puncture test of secondary batteries
[0296] At 25°C, charge the secondary battery at a constant current of 1C to 4.2V, continue constant voltage charging until the current is ≤0.05C, and let it stand for 5 minutes. At this time, the secondary battery is in a 100% SOC state. Use a high-temperature resistant steel needle with a diameter of 1mm (the cone angle of the needle tip is 30°) to perform a needle penetration test. The needle penetration speed is 0.01mm / s. Stop when the penetration depth reaches 3mm. Keep it for 60 minutes and observe whether the secondary battery fails. The judgment standard for secondary battery failure is: the voltage drops to 0V. Take 10 secondary batteries for testing and count the number of secondary batteries that pass the needle penetration test.
[0297] The more secondary batteries that pass the needle penetration test, the better the reliability of the secondary battery.
[0298] (3) Secondary battery production yield test
[0299] Place the secondary battery in the hot press test position, set the pressure to 5 MPa, the temperature to 95°C, and the hot press time to 5 seconds. Observe the instrument display. If the instrument displays OK, it is considered qualified; otherwise, it is considered abnormal. Take 100 secondary batteries for testing, and the pass rate of the hot press test is used as the secondary battery production yield.
[0300] It can be seen from the test results in Table 1 that when the isolation film includes a first base film, a second base film and an adhesive layer located between the first base film and the second base film, and the stiffness T0 of the isolation film in the transverse direction (TD) is between 1.0 mN×cm and 8.0 mN×cm, and the stiffness M0 of the isolation film in the longitudinal direction (MD) is between 1.2 mN×cm and 7.0 mN×cm, the thermal shrinkage rate of the isolation film can be reduced, the pass rate of the needle penetration test of the secondary battery can be improved, the reliability of the secondary battery can be improved, and the production yield of the secondary battery can also be improved.
[0301] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and within the scope of the technical solution of the present application, embodiments having substantially the same structure as the technical idea and exerting the same effects are all included in the technical scope of the present application. In addition, within the scope of the subject matter of the present application, various modifications that can be conceived by those skilled in the art to the embodiments, and other methods constructed by combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A separation film, comprising: First basement membrane; Second basement membrane; as well as an adhesive layer, disposed between the first base film and the second base film; The stiffness of the isolation film in the transverse direction is recorded as T0, and the stiffness of the isolation film in the longitudinal direction is recorded as M0, then T0 is 1.0-8.0 mN×cm, and M0 is 1.2-7.0 mN×cm.
2. The isolation film according to claim 1, wherein: The stiffness T0 of the isolation film in the transverse direction is 1.7-5.0 mN×cm, and can be 1.9-4.7 mN×cm; and / or, The stiffness M0 of the isolation film in the longitudinal direction is 1.2-4.0 mN×cm, and can be optionally 1.5-3.3 mN×cm.
3. The isolation film according to claim 1 or 2, wherein: T0 / M0 is 1.0-2.5, and can be optionally 1.2-2.
0.
4. The isolation film according to any one of claims 1 to 3, wherein: The stiffness of the first base film in the transverse direction is recorded as T1, T1 is 0.25-4.5 mN×cm, and can be 0.9-3.0 mN×cm; and / or, The stiffness of the first base film in the longitudinal direction is recorded as M1, M1 is 0.15-4.0 mN×cm, and can be 0.6-3.0 mN×cm; and / or, The stiffness of the second base film in the transverse direction is recorded as T2, T2 is 0.3-5.0 mN×cm, and can be optionally 0.8-3.5 mN×cm; and / or, The stiffness of the second base film in the longitudinal direction is recorded as M2, and M2 is 0.2-4.5 mN×cm, and can be optionally 0.5-3.0 mN×cm.
5. The isolation film according to claim 4, wherein: T1 / M1 is 1.0-3.0, optionally 1.2-2.0; and / or, T2 / M2 is 1.0-3.5, and can be optionally 1.1-1.
9.
6. The isolation film according to any one of claims 1 to 5, wherein: The average fiber diameter of the first base film is 80-300 nm, and can be 100-280 nm; and / or, The average fiber diameter of the second base membrane is 100-300 nm, and can be optionally 120-280 nm.
7. The isolation film according to any one of claims 1 to 6, wherein: The ratio of the crystallinity of the second base film to the crystallinity of the first base film is greater than 1, and may be 1.03-1.5, and may be 1.05-1.25; and / or, The crystallinity of the first base film is 33%-70%, and can be 35%-45%; and / or, The crystallinity of the second base film is 35%-80%, and can be 40%-55%.
8. The isolation film according to any one of claims 1 to 7, wherein: The ratio of the thickness of the second base film to the thickness of the first base film is greater than 1, and may be 1.02-5.0, and may be 1.2-2.5; and / or, The thickness of the first base film is less than or equal to 12 μm, and can be 2.5-5 μm; and / or, The thickness of the second base film is less than or equal to 14 μm, and can be optionally 3-6 μm.
9. The isolation film according to any one of claims 1 to 8, wherein: The ratio of the melting point of the first base film to the melting point of the second base film is less than 1, and may be 0.2-0.95, and may be 0.35-0.90; and / or, The melting point of the first base film is greater than or equal to 110° C., and can be 120° C.-165° C.; and / or, The melting point of the second base film is greater than or equal to 150°C, and can be optionally 165°C-330°C.
10. The isolation film according to any one of claims 1 to 9, wherein: The ratio of the porosity of the second base film to the porosity of the first base film is greater than 1, and may be 1.01-2.8, and may be 1.1-2.0; and / or, The porosity of the first base film is 28%-70%, and can be 30%-50%; and / or, The porosity of the second base film is 30%-80%, and can be 35%-60%; and / or, The porosity of the isolation membrane is 27%-65%, and can be optionally 33%-55%.
11. The isolation film according to any one of claims 1 to 10, wherein: The ratio of the average pore size of the second base film to the average pore size of the first base film is greater than 1, and may be 1.05-2.5, and may be 1.1-2; and / or, The average pore size of the first base film is 48-1800 nm, and can be 50-300 nm; and / or, The average pore size of the second base film is 50-2000 nm, and can be optionally 100-400 nm.
12. The isolation film according to any one of claims 1 to 11, wherein: The ratio of the air permeability of the first base film to the air permeability of the second base film is greater than 1, and may be 1.05-3.0, and may be 1.08-2.0; and / or, The air permeability of the first base film is less than or equal to 300s / 100cc, and can be 120-260s / 100cc; and / or, The air permeability of the second base film is less than or equal to 250s / 100cc, and can be optionally 110-220s / 100cc.
13. The isolation film according to any one of claims 1 to 12, wherein: The first base film and the second base film each independently include one or more of polyolefins and derivatives thereof, halogenated polyolefins and derivatives thereof, polyethers and derivatives thereof, polyetheretherketones and derivatives thereof, polyesters and derivatives thereof, polyimides and derivatives thereof, and polyvinyl alcohols and derivatives thereof; Optionally, the halogenated polyolefin and its derivatives include one or more of polytetrafluoroethylene and its derivatives, polyvinyl fluoride and its derivatives, polyvinylidene fluoride and its derivatives; Optionally, the polyester and its derivatives include one or more of polyethylene terephthalate and its derivatives, polybutylene terephthalate and its derivatives.
14. The isolation film according to any one of claims 1 to 13, wherein: The bonding layer includes a binder; Optionally, the bonding layer includes a binder and a filler; Optionally, the binder includes one or more of polyacrylate, polyacrylic acid, polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-trichloroethylene copolymer, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, carboxymethyl cellulose, hydroxypropyl cellulose, regenerated cellulose, cellulose acetate, cellulose acetate propionate, cellulose acetate butyrate, polyacrylonitrile, polyvinyl alcohol, polyethylene, polypropylene, starch, and cyanoethyl pullulan; Optionally, the filler includes at least one of inorganic particles, organic particles, and organic-metal framework materials; Optionally, the inorganic particles include one or more of inorganic particles having a dielectric constant of 5 or more, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions; Optionally, the organic particles include one or more of polycarbonate, polythiophene, polypyridine, polystyrene, polyacrylic wax, polyethylene, polypropylene, cellulose, cellulose modifier, melamine resin, phenolic resin, polyester, silicone resin, polyimide, polyamideimide, polyaramid, polyphenylene sulfide, polysulfone, polyethersulfone, polyetheretherketone, polyaryletherketone, and copolymer of butyl acrylate and ethyl methacrylate; Optionally, the organic-metal framework material includes one or more of a nitrogen-containing heterocyclic ligand building structure, an organic carboxylic acid ligand building structure, and a nitrogen-oxygen mixed ligand building structure.
15. The isolation film according to any one of claims 1 to 14, wherein: The thickness of the adhesive layer is greater than or equal to 0.3 μm, and can be 0.5-4 μm; and / or, The surface density of the adhesive layer is 1.0-6.0 g / m 2 , optional 1.2-5.0g / m 2 and / or, The bonding strength between the adhesive layer and the first base film is greater than or equal to 3N / m, and can be 4-15N / m; and / or, The bonding strength between the adhesive layer and the second base film is greater than or equal to 3 N / m, and can be 4-15 N / m.
16. The isolation film according to claim 14 or 15, wherein: The content of the binder is greater than or equal to 10%, and can be 10%-30%, based on the total weight of the adhesive layer; and / or, The content of the filler is less than or equal to 90%, and can be 60%-80%, based on the total weight of the adhesive layer; and / or, The volume distribution particle size Dv50 of the filler is less than or equal to 1.5 μm, and can be optionally 0.1-1.4 μm.
17. The isolation film according to any one of claims 1 to 16, wherein: The isolation film satisfies at least one of the following conditions (1) to (4): (1) The transverse tensile strength of the separator is greater than or equal to 700 kg / cm 2 , can be selected as greater than or equal to 1000kg / cm 2 ; (2) The longitudinal tensile strength of the isolation film is greater than or equal to 1000 kg / cm 2 , can be selected to be greater than or equal to 1200kg / cm 2 ; (3) The transverse heat shrinkage rate of the isolation film at 250° C. for 1 hour is less than or equal to 5%, and can be less than or equal to 2%; (4) The longitudinal heat shrinkage rate of the isolation film at 250° C. for 1 hour is less than or equal to 5%, and can be optionally less than or equal to 2%.
18. A secondary battery comprising the separator according to any one of claims 1 to 17.
19. The secondary battery according to claim 18, wherein The secondary battery comprises a positive electrode sheet and a negative electrode sheet, the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the first base film of the separator faces the negative electrode sheet, and the second base film of the separator faces the positive electrode sheet.
20. An electrical device comprising the secondary battery according to claim 18 or 19.